English education for healthcare professionals in Japan. Issue 4 (November 2017) - Moross, Janelle; Seki, Naoko; Morio, Ikuko
Summary: In a global environment, education for healthcare professionals should include cultivating human resources who have the necessary skills to work in an international arena. This article will review the current status of English education for dental healthcare professionals in Japan. After conducting a literature search using the keywords: English education, Japan, and dental, only a few studies were found that investigated and proposed suggestions for dental professional English education. Even so, these were still in the early stages with outcomes yet to be fully evaluated. Even though English is thought indispensable for global professionals, and that increasing chances for communication skills is necessary, little attention has been addressed to English education for dental professionals or the implementation of such education in the Japanese undergraduate dental curricula. With the current reality of field expansion in dentistry, the need for not only improved English communication skills for Japanese dentists, but also the acquisition of essential expertise, psychomotor, teambuilding, critical thinking, and creative thinking skills in English as well as Japanese, is a definite probability. In order to reach this level of knowledge, further efforts and research would be necessary for the advancement and development of dental professional English education in Japan.